(untitled) (Global Journal of Management and Business Research, 2017)
In order to deliver service in quality specially in banking system the queuing model was appropriate in order to suggest waiting time, service rate and etc for efficient service delivery of better implementation of banking system. Comparative study of two selected banks (Commercial Bank of Ethiopia & Dashen Bank) in Wolaita zone of Ethiopia was investigated. The queuing model was employed for both banking system in order to measure the behavioral queuing characteristics of customers in terms of their arrival and service rate respectively. The data for the arrival and service rate of the two banks were collected by observation methods for two days of a week simultaneously. The result revealed that on average 10.2 and 8.6 customers arrive and served per hours, respectively in Commercial Bank of Ethiopia Tona branch.